Paternally Inherited P-Element Copy Number Affects the Magnitude of Hybrid Dysgenesis in Drosophila simulans and D. melanogaster. (27th April 2020) - Serrato-Capuchina, Antonio; Wang, Jeremy; Earley, Eric; Peede, David; Isbell, Kristin; Matute, Daniel R
Abstract: Transposable elements (TEs) are repetitive regions of DNA that are able to self-replicate and reinsert themselves throughout host genomes. Since the discovery of TEs, a prevalent question has been whether increasing TE copy number has an effect on the fitness of their hosts. P -elements (PEs) in Drosophila are a well-studied TE that has strong phenotypic effects. When a female without PEs (M) is crossed to a male with them (P), the resulting females are often sterile, a phenomenon called hybrid dysgenesis (HD). Here, we used short- and long-read sequencing to infer the number of PEs in the genomes of dozens of isofemale lines from two Drosophila species and measured whether the magnitude of HD was correlated with the number of PEs in the paternal genome. Consistent with previous reports, we find evidence for a positive correlation between the paternal PE copy number and the magnitude of HD in progeny from ♀M × ♂ P crosses for both species. Other crosses are not affected by the number of PE copies. We also find that the correlation between the strength of HD and PE copy number differs between species, which suggests that there are genetic differences that might make some genomes more resilient to the potentially deleterious effects of TEs. Our results suggest that PE copy number interacts with other factors in the genome and the environment to cause HD and that the importance of these interactions is species specific.